The Influence of Conduct Problems and Callous-Unemotional Traits on Academic Development Among Youth. - Horan, Jacqueline; Brown, Joshua; Jones, Stephanie; Aber, J. (Journal of Youth & Adolescence, 2016)
The present study attempted to address developmental differences within the large group of youth with conduct problems through an examination of the relationship between callous-unemotional traits and academic outcomes in an effort to expand the field's understanding of heterogeneity in outcomes associated with behavior problems. Data were collected from a cohort of 3rd grade students ( N = 942; 51 % female; 45.6 % Hispanic/Latino, 41.1 % Black/African American, 4.7 % Non-Hispanic White; mean age = 8.07 years) in eighteen public elementary schools, as well as their parents and teachers. Hierarchical linear modeling revealed that callous-unemotional traits were associated with lower quality student-teacher relationships and worse performance on standardized math and reading exams over and above the effects of conduct problems. These findings suggest that school-based interventions may be particularly effective in ameliorating some of the deficits noted within this subset of youth exhibiting conduct problems. This finding has important policy implications as the field of developmental science attempts to design and enrich programs that focus on improving social-emotional learning.